Utilização do sinal de fundo e calibração multivariada como um procedimento para acessar a concentração total de concomitantes em espectrometria de absorção atômica com forno tubular na chama e aerossol térmico (TS-FF-AAS) - Miranda, Kelber dos Anjos de (2009)
TS-FF-AAS employs a metal tube atomizer above an air/acetylene flame and in this case, the atoms residence time is longer than that observed in FAAS (Flame AAS). As a result, elevated background signals are obtained. For this reason, a study about the effects of the concomitants Ca, Cu, Fe, K, Mg, Mn, Na and Zn on the analytical signals of Cd and Pb with the help of factorial design was performed initially. Cadmium and Pb analytical signals were not significantly affected by the presence of concomitants. Although, the main purpose of this study was to make use of background signals and multivariate calibration as a procedure to assess the total concentration of concomitants in Thermospray Flame Furnace Atomic Absorption Spectrometry (TS-FF-AAS). Background signals of 29 solutions containing Cd (25 g/L), Pb (500 g/L) and four concomitants (Ca, K, Mg and Na – total concentration values ranging from 0 to 5.52 g/L) were recorded at two wavelengths: 228.8 Cd and 283.3 nm Pb. With the help of Partial Least Squares (PLS), calibration models using either each wavelength alone or a combination of both were constructed to predict the total concentration of concomitants. The best model showed Root Means Square Errors of Validation (RMSEV) of 0.35 g/L using background signals at 283.3 nm. A pharmaceutical sample containing 3 g/L (sum of Ca, K, Mg and Na) was analyzed and 3% was the relative error. This sample and those used in the calibration and validation sets were also analyzed using X-ray fluorescence (XRF) and a good agreement was observed. This study extends the possibilities for the use of background signals in spectrometric techniques.